Effectiveness and Efficiency of Trichoderma sp. Multiplication on Different Growing Media - Irianti, Agnes Tutik Purwani; Rahayu, Sri; Ayen, Rosalina Yuliana; Oktarianti, Sherly (CROPSAVER - Journal of Plant Protection, 2025)
Trichoderma sp. is a fungus that plays an important role as a biological control agent, commonly mass-produced using rice and corn as media. The high cost of rice and corn can become an obstacle in the mass production of Trichoderma sp. fungus. To reduce production costs, an economical solution needs to be sought by using more affordable and readily available growth media. This study aims to test the effectiveness and efficiency of Trichoderma sp. propagation using various types of growth media. The research employed a laboratory experimental method with a completely randomized single-factor design, which is the type of media. The treatments are as follows: T1: Rice, T2: Corn, T3: Sugarcane Bagasse, T4: Bran, T5: Rice + Bran, T6: Corn + Bran, T7: Rice + Sugarcane Bagasse (1:1), T8: Corn + Sugarcane Bagasse (1:1), T9: Rice + Sugarcane Bagasse + Bran (1:1:1), T10: Corn + Sugarcane Bagasse + Bran (1:1:1). Each treatment consisted of three replications. Furthermore, to determine the effect of treatments on the observed variables, analysis of variance (ANOVA) was performed using an F-test at a significance level of 5% and 1%. The results showed that the type of propagation medium had a highly significant effect on the density and viability of Trichoderma sp. conidia. The most effective medium for Trichoderma sp. propagation, in terms of conidia density, was treatment T8 (3.27 x 10^9), while in terms of conidia viability, the most effective treatment was T2 (96.80%). The most efficient treatment for propagating Trichoderma sp. was T4 (Bran medium).